METHOD OF EXTRACTING SIGNIFICANT COMPONENTS FOR ASSESSING THE VARIABILITY OF THE PULSE WAVE FORM - Saidmurodov Samandar Abdumalik o’g’li (Web of Journals Publishing, 2025)
The generally accepted approach to pulse wave analysis is based on the assessment of its shape features within each cardio interval. In this case, a set of indices (cardiac efficiency index, reflection index, stiffness index) is calculated, which are determined by the reference points of the waveform. The authors propose an alternative method based on harmonic analysis of the resampled signal for each of the cardio intervals and has a number of advantages in studying the variability of the pulse waveform separately from the variability of its rhythm. The results of a pilot series of experiments using the new method indicate its promise in solving the problems of restoring the central pulse from distal measurements.
Keywords: Pulse wave, harmonic analysis, rheography, central pulse, pulse waveform variability.